OPTICAL, CORROSION, AND ELECTROCHEMICAL ANALYSIS OF GRAPHITE–TURMERIC EXTRACT FORMULATIONS FOR ZINC IN 3.5 wt.% NaCl SOLUTION - Romi Fadli Syahputra; Neneng Fitrya; Delovita Ginting; Fauzan Fahturrahman; Salsabila Marcela; Aas Wiranda; Salsabillah Ratih Putri; Putri Fitri Handayani; Bunga Meyzia; Zulkarnain Zulkarnain (Universitas Mataram, 2026)
The development of environmentally friendly corrosion protection materials is important for protecting metallic components exposed to saline environments. In this work, graphite–curcuminoids hybrid formulations based on curcuminoids extracted from Curcuma longa and graphite (IGC) were evaluated for corrosion protection of zinc in 3.5 wt.% NaCl solution. Optical properties were characterized by UV–Vis spectroscopy, while corrosion behavior was assessed using linear sweep voltammetry and Tafel polarization analysis. The incorporation of graphite modified the absorption characteristics of curcuminoids and slightly reduced the optical band gap from 2.65 eV (curcuminoids) and 2.85 eV (graphite) to 2.59–2.62 eV for the hybrid formulations. Among the investigated compositions, IGC1 exhibited the best performance, reducing the corrosion rate from 0.1175 to 0.0408 mm/y and achieving an inhibition efficiency of 65.3%. In contrast, IGC2 showed a higher corrosion rate of 0.1863 mm/y, indicating that excessive graphite loading adversely affected the protective performance. The results indicate that the corrosion behavior of graphite–curcuminoids hybrid formulations is highly dependent on composition. These findings demonstrate the potential of graphite–curcuminoids hybrids as environmentally friendly corrosion inhibitors for zinc in saline water media.